UNDERSTANDING THE MEANING OF GOD’S LEGISLATION: Critical Analysis of Islamic Law Reasoning Criticism in Indonesia - Ipandang, Ipandang (Fakultas Syariah, 2020)
The existence of Islamic law in dealing with social problems is questioned. The authoritative claim on the establishment of Islamic law by certain ulama organization is presumed to weaken the role of Islamic law in society. This article aims to analyze the legal reasoning structure and interpretation model of mufti (the one issuing fatwa) in establishing Islamic law. This article is based on the doctrinal legal research with conceptual approach, particularly on the thought of Khaled M. Abou El Fadl. By going through the analysis process of critical negotiation, there will be constructive dialectic to produce a humanistic Islamic law. This article found that the authority of textual meaning needs to be placed on top of the authority of mufti. The structured legal reasoning will silence the tafsir plurality on religious texts. The stagnation of this fatwa can be bridged via open Hermeneutics method which is dialectic among the author, text, reader, and the target discourse. So, fatwa can be the fundamental solution of the social problem which is humanistic.Eksistensi hukum Islam dalam menangani masalah sosial kemasyarakatan mulai diragukan. Klaim otoritas penetapan hukum Islam oleh organisasi ulama tertentu disinyalir menjadi sebab melemahnya peran hukum Islam dalam masyarakat. Artikel ini bertujuan menganalisis struktur nalar hukum dan model interpretasi pemberi fatwa dalam penetapan hukum Islam. artikel ini berasal dari penelitian hukum doctrinal dengan konseptual khususnya pemikiran Khaled M. Abou El Fadl. Karena melalui proses analisis negosiasi kritis, akan muncul dialektika yang konstruktif untuk menghasilkan hukum Islam yang humanis. Artikel ini menemukan bahwa otoritas makna teks perlu diposisikan di atas kewenangan pemberi fatwa.Â Penalaran hukum yang terlembaga akan mendorong pembungkaman pluralitas tafsir teks agama. Kebekuan hasil fatwa ini dapat dijembatani melalui metode hermeneutika terbuka yang bersifat dialektis, antara pengarang, teks, pembaca, dan sasaran wacana. Sehingga fatwa dapat menjadi sandaran penyelesaian problem sosial kemasyarakatan yang humanis.